2018
DOI: 10.3389/fpls.2018.00718
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis AtUNC-93 Acts as a Positive Regulator of Abiotic Stress Tolerance and Plant Growth via Modulation of ABA Signaling and K+ Homeostasis

Abstract: Potassium (K+) is one of the essential macronutrients required for plant growth and development, and the maintenance of cellular K+ homeostasis is important for plants to adapt to abiotic stresses and growth. However, the mechanism involved has not been understood clearly. In this study, we demonstrated that AtUNC-93 plays a crucial role in this process under the control of abscisic acid (ABA). AtUNC-93 was localized to the plasma membrane and mainly expressed in the vascular tissues in Arabidopsis thaliana. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Pair-wise comparisons of Otis and Baronesse's response to drought stress showed only 37 and 61 significant DAS genes, respectively, and only 6 genes were common between the two genotypes ( Table 1 ; Supplementary Figure 2 ; Supplementary Tables 18–22 ). Of the 6 genes showing significant changes in AS in both genotypes, BART1_0-u33753 (HORVU5Hr1G021770) has similarity to unc-93 homolog A, a positive regulator of abiotic stress tolerance in Arabidopsis (Xiang et al, 2018 ). This showed a complete reversal of the most abundant transcript BART1_0-u33753.005 in the watered samples of both genotypes to the BART1_0-u33753.001 transcript which was most abundant in drought samples ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 99%
“…Pair-wise comparisons of Otis and Baronesse's response to drought stress showed only 37 and 61 significant DAS genes, respectively, and only 6 genes were common between the two genotypes ( Table 1 ; Supplementary Figure 2 ; Supplementary Tables 18–22 ). Of the 6 genes showing significant changes in AS in both genotypes, BART1_0-u33753 (HORVU5Hr1G021770) has similarity to unc-93 homolog A, a positive regulator of abiotic stress tolerance in Arabidopsis (Xiang et al, 2018 ). This showed a complete reversal of the most abundant transcript BART1_0-u33753.005 in the watered samples of both genotypes to the BART1_0-u33753.001 transcript which was most abundant in drought samples ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 99%
“…The other MTA was detected associated with GY-STI, HI-GMP, HI-STI, SPAD-GMP, and SPS-GMP on chromosome 5A (Tdurum_contig76578_537) at 110,830,599 bp, annotated as UNC93-like protein. Likewise, a study indicated that UNC93 functions as a positive regulator of drought stress tolerance via ABA-dependent signal transduction pathways (Xiang et al, 2018 ). An MTA was detected associated with GY-RDI on chromosome 7A (Excalibur_c24593_1217) at 7,721,495 bp, annotated as cytochrome P450 family protein.…”
Section: Discussionmentioning
confidence: 99%
“…In C. elegans, UNC-93 was shown to indirectly regulate K + fluxes by modulating the function of K + channels (de la Cruz et al, 2003), although it is unclear whether this regulation depends on a transporter function. The At3g09470 gene, the sole member of the Arabidopsis UNC-93-like family (Figure 2), was shown to participate in K + homeostasis and in ABA-mediated stress responses (Xiang et al, 2018), but again its mode of action remains unknown. It could well be that, like its C. elegans homolog, At3g09470 regulates K + fluxes indirectly.…”
Section: The Nag-t and Nodulin-like Transporter Families With Potentimentioning
confidence: 99%